PARENTS’ INVOLVEMENT IN NON-FORMAL EDUCATION PROGRAM “KELAS MANDIRI” IN KOTA SENTANI - Ivona Dorobia (Journal of Innovation Research and Knowledge, 2025)
The role of parents is very important in formal education, non-formal education and informal education. The purpose of this study was to investigate parental involvement in their children's education within a non-formal educational setting. The study focused on parents with children enrolled in the Papua Language Institute's English Class program called “Kelas Mandiri”. It employed a qualitative research design and collected data through observation, in-depth interviews, and Focus Group Discussions (FGD). The data were analyzed using Miles & Huberman's three-stage qualitative data analysis. The study found that parental involvement in supporting children in the "Kelas Mandiri" is relatively low due to limited educational resources, financial constraints, health issues, cultural events, marital relationships, and global changes. The implications suggest an increased focus on the religious approach within the community and family, as well as the development of non-formal programs. It is crucial to educate parents about their essential role in their children's lives and implement strategies to enhance their involvement in their children's learning at home